Cárie dentária em pacientes com anemia falciforme em uma coorte brasileira - Menezes, Fabrício dos Santos (2013)
The scientific evidence for the interactions between sickle cell anemia (SCA) and dental caries remains poor despite the social and epidemiological importance of these diseases. This synergistic effect may contribute to the increased morbidity and, in final instances, mortality, once that oral infections have been related to sickle cell crises. The present cross-sectional study aimed at investigating the caries experience in a Brazilian cohort SCA. Eligible patients identified by alkaline pH hemoglobin electrophoresis were examined regarding oral and nutritional conditions. Complementary data were obtained from medical records and questionnaire. Patients were divided into two groups: (i) 97 individuals presenting high caries experience, and (ii) 90 caries-free individuals or who presented either low or moderate caries experience. The high caries experience was associated with avascular necrosis of femur (P=0.033), syncope (P=0.028), fetal hemoglobin less than 10% (P=0.034), permanent dentition (P=0.002), daily dental floss (P=0.007), toothpaste with fluoride (P=0.037), visible plaque (P=0.027), low salivation (P=0.006) and last visit to the dentist in less than 12 months (P=0.000). Logistic regression detected positive association between high caries experience and age, permanent dentition, low salivation, intrinsic tooth opacity and syncope. Other classical risk factors for dental caries were not significant. These data suggest the hypothesis that SCA harms natural defenses and make affected patients more susceptible to increased caries experience.